All this hell : U.S. nurses imprisoned by the Japanese - Monahan, Evelyn (University Press of Kentucky, 2010)
""Even though women were not supposed to be on the front lines, on the front lines we were. Women were not supposed to be interned either, but it happened to us. People should know what we endured. People should know what we can endure.""--Lt. Col. Madeline Ullom More than one hundred U.S. Army and Navy nurses were stationed in Guam and the Philippines at the beginning of World War II. After the Japanese attack on Pearl Harbor in December 1941, five navy nurses on Guam became the first American military women of World War II to be taken prisoner by the Japanese. More than seventy army nurses su